Pravni izzivi vloge delavskih predstavnikov v organih upravljanja gospodarskih družb - Franca, Valentina (Delavci in delodajalci, 2016)
The paper focuses on the role of workers' representatives in management bodies of business companies, particularly regarding the realisation of the role of workers' representatives in these bodies in relation to the purpose of the legal regulations. According to the analysis of the national legislation, the case law and the findings of international research, there are certain shortcomings which could be partly remedied by a change in legislation and partly with other activities aimed at realisation of worker participation.
Keywords: gospodarske družbe; pravna ureditev; soupravljanje; uprava; upravljanje; zaposleni